2018
DOI: 10.3390/su10093134
|View full text |Cite
|
Sign up to set email alerts
|

How to Develop the Interdisciplinary Innovation Teams Sustainably?—A Simulation Model from a Perspective of Knowledge Fission and Fusion

Abstract: Knowledge interaction is vital in order that interdisciplinary innovation teams (IITs) develop sustainably. This paper aims to reveal the laws of knowledge interaction in IITs from a perspective of knowledge fission and fusion. Herein, the conceptions of knowledge fission to depict the team member’s divergent thinking and knowledge fusion to depict the team member’s convergent thinking based on the concept of social physics are proposed. Furthermore, the Markov process describing knowledge interaction is built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…For sustainability, Cheng and Zhang believed that the sustainability of innovation teams included the ongoing operation of the team, guarantee of the team members' benefit, the sustainable innovation of the team and other factors [26]. Some studies demonstrated that the sustainability of innovation teams is directly related to team composition, team member's communication, cooperation, integration and other factors directly related to the teamwork quality and team structure.…”
Section: Success and Sustainability Of The Creative Research Group (Smentioning
confidence: 99%
See 4 more Smart Citations
“…For sustainability, Cheng and Zhang believed that the sustainability of innovation teams included the ongoing operation of the team, guarantee of the team members' benefit, the sustainable innovation of the team and other factors [26]. Some studies demonstrated that the sustainability of innovation teams is directly related to team composition, team member's communication, cooperation, integration and other factors directly related to the teamwork quality and team structure.…”
Section: Success and Sustainability Of The Creative Research Group (Smentioning
confidence: 99%
“…Some studies demonstrated that the sustainability of innovation teams is directly related to team composition, team member's communication, cooperation, integration and other factors directly related to the teamwork quality and team structure. In this context, teamwork quality and team structure are two important factors influencing sustainability [26][27][28]. Compared to team success at the static level, team sustainability is more focused on dynamic level considerations.…”
Section: Success and Sustainability Of The Creative Research Group (Smentioning
confidence: 99%
See 3 more Smart Citations